2011
DOI: 10.1080/13548506.2010.540250
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of facial changes in scleroderma

Abstract: The physical disabilities associated with scleroderma are well known but the psychological impact of the condition has received less attention. Few studies have examined appearance related issues, most notably of the face. The aim of this study is to evaluate the psychological impact of facial, aesthetic and functional changes in scleroderma. One hundred seventy-one patients with a clinical diagnosis of scleroderma were recruited into the study. Digital photographs were objectively graded into groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…32 Appearance changes in highly visible areas of the body, particularly the face and hands, are common in patients with SSc and contribute to body image distress, which in turn can be associated with symptoms of anxiety and depression. 1,4,[32][33][34][35][36] Several cross-sectional studies have reported that appearance changes of the face, including changes to the mouth, as well as hand involvement, including skin thickening, have consistently been related to body image distress, including dissatisfaction with appearance, decreased appearance selfesteem, and symptoms of anxiety and depression. [32][33][34][35][36] Other appearance changes, including telangiectasias, may also be associated with body image distress.…”
Section: Body Imagementioning
confidence: 99%
“…32 Appearance changes in highly visible areas of the body, particularly the face and hands, are common in patients with SSc and contribute to body image distress, which in turn can be associated with symptoms of anxiety and depression. 1,4,[32][33][34][35][36] Several cross-sectional studies have reported that appearance changes of the face, including changes to the mouth, as well as hand involvement, including skin thickening, have consistently been related to body image distress, including dissatisfaction with appearance, decreased appearance selfesteem, and symptoms of anxiety and depression. [32][33][34][35][36] Other appearance changes, including telangiectasias, may also be associated with body image distress.…”
Section: Body Imagementioning
confidence: 99%
“…Patients’ psychosocial well-being is often affected more by disfigurement caused by facial changes (e.g. telangiectasias, loss of vermillion border of the lip, pronounced vertical perioral lines) and hand contractures than occult visceral disease 122 . Patients with disfiguring lesions can have appropriate cosmetic intervention.…”
Section: Treatment Approachmentioning
confidence: 99%
“…Nonetheless, existing studies have shown that more severe disease manifestations, such as significant skin changes in the hands, are associated with greater body image dissatisfaction, increased depressive symptoms, and reduced overall psychosocial functioning, including appearance-related anxiety and social avoidance [7][9]. One recent study of 171 SSc patients examined the impact of facial changes, and reported that patients rated facial disfigurement as the most worrying aspect of the condition [10], and another study of 129 SSc patients reported that greater objective disfigurement was linked to more distress, worry, and perceptions of noticeability by patients [9].…”
Section: Introductionmentioning
confidence: 99%